Enhancing Madrasa Teacher Mindfulness through Organizational Culture - Hasan Baharun; Imam Bukhori; Fatimatus Zahro (Journal of Innovation in Educational and Cultural Research, 2025)
This research explores the role of organizational culture in enhancing teacher mindfulness in madrasas, viewed through the lens of Schein's organizational culture theory. A qualitative case study approach was employed, utilizing interviews, observations, and documentation as data collection techniques. Data analysis followed a three-step process: data reduction, presentation, and conclusion drawing. The findings reveal that three key elements of organizational culture significantly contribute to increasing teacher mindfulness. First, organizational culture artifacts, such as outing class activities and the 3S slogan (Greetings, Smile, Greet), play a vital role. Second, the espoused beliefs and values reflect the madrasa's unique vision, particularly the fifth content of the Five Santri Awarenesses—organizational awareness. Third, the underlying assumption is that integrating technology and open dialogue in madrasa activities and learning fosters a strong and influential organizational culture. This study highlights the importance of organizational culture in fostering teacher mindfulness, leading to a more harmonious and effective work environment that enhances educational quality.